BAGIAN AYAH DAN SAUDARA DALAM KEWARISAN ISLAM DI INDONESIA (Perspektif Fiqh, KHI dan Prakteknya di PA dan Masyarakat) (Mazahib, 2012)
After the Compilation of Islamic Law, it appears that not only applied Shafi opinion, but wider use other teachings, known as the "replacement heir" and "testament wajibah" that the Sunni doctrine does not exist. Renewal in Islamic inheritance law can be seen also in some other rules. Rules of the father and mother when the heir did not leave a child (which is commonly known in terms gharawain fiqh), the siblings and relatives of the mother when the heir to the state to lose (in terms of fiqh, commonly known by the term Musharaka) and the brothers when with children female. Rules that have made this seem confusing and lead to different interpretations, and caused debate among the 'ulama as well as law enforcement in Indonesia.